Structure of the Lectin MRH Domain of Glucosidase II, an Enzyme that Regulates Glycoprotein Folding Quality Control in the Endoplasmic Reticulum - Olson, Linda J. (2013)
Here we report for the first time the three-dimensional structure of a mannose 6-phosphate receptor homology (MRH) domain present in a protein with enzymatic activity, glucosidase II (GII). GII is involved in glycoprotein folding in the endoplasmic reticulum. GII removes the two innermost glucose residues from the Glc3Man9GlcNAc2 transferred to nascent proteins and the glucose added by UDP-Glc:glycoprotein glucosyltransferase. GII is composed of a catalytic GII subunit and a regulatory GII subunit. GII participates in the endoplasmic reticulum localization of GII and mediates in vivo enhancement of N-glycan trimming by GII through its C-terminal MRH domain. We determined the structure of a functional GII MRH domain by NMR spectroscopy. It adopts a -barrel fold similar to that of other MRH domains, but its binding pocket is the most shallow known to date as it accommodates a single mannose residue. In addition, we identified a conserved residue outside the binding pocket (Trp-409) present in GII but not in other MRHs that influences GII glucose trimming activity.